Predictors of Self-Determination and Mental Health Symptoms Among Youth in Juvenile Justice Facilities. (May 2021) - Houchins, David E.; Jimenez, Eliseo; Langley, Nickolas; Plescow, Katelyn; Henrich, Christopher C.
The purpose of this article was to examine the relationships between (a) youth and facility characteristics and (b) youth risk and resilience factors (i.e., mental health, self-determination [SD]) in juvenile justice facilities. Extant self-report data from 205 nationally representative correctional facilities and 7, 073 youth, collected as part of the Office of Juvenile Justice and Delinquency Survey of Residential Placement, were analyzed. Youth charateristics included sex, race, disability classification, mental health status, traumatic events/abuse encountered, offense committed, and SD. Facility factors included facility climate and counseling services. Results indicated that both prior abuse and victimization in the facility were positively correlated with mental health symptoms and SD. Positive perceptions of facility climate were associated with lower mental health symptoms. Youth who were female, younger, with a learning disability, and had committed a violent offense, reported more mental health symptoms. Positive perceptions of facility climate and receipt of counseling in the facility were associated with higher SD. Contrary to expectations, prior abuse and victimization in the facility were associated with higher SD. Recommendations include creating positive facility climates, developing targeted SD instruction, and providing tailored counseling services to facilitate successful transitions out of juvenile justice.